Pengaruh Inovasi Produk, Literasi Keuangan, dan Kredit Usaha Rakyat, Terhadap Kinerja UKM Konveksi Kota Tangerang Selatan - Izhar Hilmi Pranowo; Eliada Herwiyanti; Mafudi Mafudi (Pascasarjana Universitas Jenderal Soedirman, 2022)
This study aims to analyze and examine the effect of people's business credit (KUR), financial literacy, and product innovation on the performance of convection SMEs in South Tangerang City. This study uses the Planned of Behavior (TPB) theory as the basis for submitting research hypotheses. The population in this study is convection SMEs in South Tangerang City, which is registered in the data of the Ministry of Cooperatives and SMEs. The sampling technique used was purposive sampling until 85 research samples were found. The results show that KUR and financial literacy affect the performance of SMEs, while product innovation does not affect the performance of SMEs. Among the independent variables, financial literacy turned out to be the dominant influence. This research theoretically supports TPB, where humans will do something as planned if the behavior is believed to provide benefits for themselves. The results of this study imply that convection SMEs are aware that their business performance will be better by having financial literacy. In terms of KUR, the low level of business actors in understanding KUR impacts low business performance. Meanwhile, innovation in the convection business does not affect performance because, until now, the government is still implementing import policies, so domestic production is indirectly still challenging to develop.